Efficacy of assistive technology interventions - Edyburn, Dave L. (Bingley, U.K. : Emerald, 2015)
The Advances in special education technology series is designed to focus international attention on applications of technology for individuals with disabilities. Outstanding researchers from around the world will contribute chapters synthesizing the research evidence on specific types of technology interventions that improve access, engagement, and learning outcomes of diverse learners. The scope of contributions will cover subfields known as assistive technology, instructional design, instructional technology, online learning, personalized learning, and universal design for learning and will encompass both formal (i.e., school) and informal learning settings (i.e., self-directed, museums) across the lifespan (i.e., preschool - adult).
Expanding the use of assistive technology while mindful of the need to understand efficacy / Dave L. Edyburn -- Assistive technology in schools : lessons learned from the national assistive technology research institute / Margaret E. Bausch, Melinda Jones Ault, Ted S. Hasselbring -- Research synthesis of studies for promoting parent and practitioner use of assistive technology and adaptations with young children with disabilities / Carl J. Dunst, Deborah W. Hamby -- Speech-generating devices in the lives of young people with severe speech impairment : what does the non-speaking child say? / Kathy L. Look Howery -- Students with visual impairments : considerations and effective practices for technology use / Frances Mary D'Andrea,Yue-Ting Siu -- Assistive technology provision for people with disabilities in Newfoundland and Labrador, Canada / Valerie M. Penton -- Assistive technology standards and evidence-based practice : early practice and current needs / Elizabeth M. Dalton -- Learning from experience : understanding assistive technology knowledge and skills through an online community of practice / Brian W. Wojcik -- Experiences of families seeking funding for assistive technologies for children with disabilities : awareness of legal mandates / Denise J. Frankoff -- Case study of a state assistive technology fund / Cindy L. Ollis, Martin E. Blair.
Print version record
Keywords: Education -- Special Education -- General; Teaching of students with specific learning difficulties/needs.; Self-help devices for people with disabilities; Rehabilitation technology